Nyssa aquatica, Water Tupelo - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana (EDIS)
FOR 262, a 2-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, and Heather V. Quintana, describes this native deciduous tree found in the bottomlands, floodplains, and swamps of southern Virginia, south to northwest Florida, west to southeastern Texas, and north through the Mississippi River Valley – scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, June 2010.